CHARACTERIZATION OF BIOLOGICAL ORGANISMS THROUGH ELECTRONIC MICROSCOPY - Cañón Bermúdez, Juan David
Electron microscopy is a characterization technique that allows to reach measurement scales in nanometers. This microscope has the ability to analyze mainly conductive samples, but in the analysis of biological samples it is essential to make a coating which allows that at the time of the analysis no electric charge concentrations are generated that make it impossible to observe them; for this our research question consists in determining what are the appropriate treatment conditions of the sample so that it is easily observable.